Management considerations for clinically relevant findings on expanded carrier screening in a sperm donor applicant population - Lauren Isley, M.S., C.G.C.; Pamela Callum, M.S., C.G.C.; Jennifer Luque, M.S., C.G.C.; Jessica Park, M.S., C.G.C.; Kara Baldwin, M.S., C.G.C. (F&S Reports, 2023)
Objective: To describe the clinical experience of managing expanded carrier screening (ECS) results in sperm donor applicants at a sperm bank in the United States, including considerations around suitability determination and appropriate education of prospective donors and recipients. Design: A retrospective review of donor genetic screening records from July 2017 to December 2021. Setting: A U.S.-based sperm bank. Patients: Donor applicants at a sperm bank. Intervention: Not applicable. Main Outcome Measures: To examine the rate of potentially significant health risks on the basis of ECS results to inform donor management and donor/recipient counseling considerations. Results: Nearly 2% of donor applicants were identified as having potentially significant health risks on the basis of their ECS results, and most individuals had no clinical manifestations related to these findings. Conclusion: There are unique challenges related to ECS in third-party reproduction for gamete providers, recipients, and their healthcare providers. A collaborative, multidisciplinary approach is necessary to help mitigate risks to donor offspring and maximize patient experience. Informed consent and access to a trained genetics professional are paramount when facilitating ECS on donor applicants and disseminating results to recipients.